2017
DOI: 10.1371/journal.pntd.0005904
|View full text |Cite
|
Sign up to set email alerts
|

Human macrophages differentiated in the presence of vitamin D3 restrict dengue virus infection and innate responses by downregulating mannose receptor expression

Abstract: BackgroundSevere dengue disease is associated with high viral loads and overproduction of pro-inflammatory cytokines, suggesting impairment in the control of dengue virus (DENV) and the mechanisms that regulate cytokine production. Vitamin D3 has been described as an important modulator of immune responses to several pathogens. Interestingly, increasing evidence has associated vitamin D with decreased DENV infection and early disease recovery, yet the molecular mechanisms whereby vitamin D reduces DENV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 56 publications
10
62
1
1
Order By: Relevance
“…A recent study determined that M2 macrophages displayed slightly higher phagocytic activity than M1 cells, and phagocytosis was not changed by treatment with 1,25(OH) 2 D 3 (36). Furthermore, MDMs treated with low-dose 1,25(OH) 2 D 3 for 6 days were less infected with dengue virus compared with untreated MDMs, which was proposed to be due to reduced viral uptake via CD206 that was down-regulated on 1,25(OH) 2 D 3 -tretated MDMs (37). In contrast, we found that CD206 was upregulated on Mtb-infected monocyte-derived cells that were polarized with a higher dose of 1,25(OH) 2 D 3 the last 20 h of 6 days differentiation.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study determined that M2 macrophages displayed slightly higher phagocytic activity than M1 cells, and phagocytosis was not changed by treatment with 1,25(OH) 2 D 3 (36). Furthermore, MDMs treated with low-dose 1,25(OH) 2 D 3 for 6 days were less infected with dengue virus compared with untreated MDMs, which was proposed to be due to reduced viral uptake via CD206 that was down-regulated on 1,25(OH) 2 D 3 -tretated MDMs (37). In contrast, we found that CD206 was upregulated on Mtb-infected monocyte-derived cells that were polarized with a higher dose of 1,25(OH) 2 D 3 the last 20 h of 6 days differentiation.…”
Section: Discussionmentioning
confidence: 91%
“…DENV infection was evaluated in PBMCs by the intracellular detection of the viral E protein using the murine monoclonal anti-flavivirus 4G2 antibody (clone D1-4G2-4-15; Millipore, Darmstadt, Germany, IgG2a) for 25 min and the respective secondary anti-mouse IgG2a-PE (Jackson ImmunoResearch, West Grove, PA) antibody for an additional 25 min at 4°in the dark. 16 These incubations were completed after the panel staining (see above), in which none of the antibodies were IgG2. For intracellular staining, PBMCs were fixed and permeabilized as discussed previously.…”
Section: Detection Of the Viral E Proteinmentioning
confidence: 99%
“…Los niveles séricos de IL-1β e IL-6 se cuantificaron por el método Enzyme-Linked ImmunoSorbent Assay (ELISA) usando un estuche comercial específico para cada citoquina (BD Biosciences, Franklin Lakes, NJ), y siguiendo las instrucciones previamente reportadas (15) . Los resultados se leyeron a una longitud de onda de 450 nm y se reportaron en pg/ml.…”
Section: Cuantificación De Il-1β E Il-6unclassified